"Que o pensamento tome a direção da sociedade": Atuação política e formulações intelectuais de Alberto Torres (1856-1917) - Favoretti, João Paulo de Souza (2021)
The final context of the imperial period in Brazil was a historic moment marked by intense political, social, economic and cultural transformations, given that the transition of regimes, the abolition of slavery, the initial steps of industrialization and the modernizing goals were striking elements of that period. In this environment of the end of the monarchic era and the began of the republican regime, Alberto Martins de Seixas Torres (1865-1917) was situated, a native of the city of Itaborai who stood out for his political, legal and intellectual performance. This narrative proposes to analyze the different phases of the author's life, focusing on a range of primary sources in order to understand the trajectory trodden by him and how the spaces of power he occupied influenced his way of dealing with existing problems. at the time and in the way of dealing with some ideas, such as that of nation, race, country and state. The objective was to capture how the social place that the intellectual from Rio de Janeiro was located was able to impact on his ideas and speeches, since Torres was a politician and jurist who had exercised functions in the three branches, occupying the positions of Constituent State Deputy of Rio de Janeiro, Federal Deputy, Minister of Justice and of Interior Affairs, President of the State of Rio de Janeiro, and, finally, before retiring, Minister of the Supreme Federal Court. As a conceptual apparatus, he resorted to the concepts of social place and social space in order to analyze how the Fluminense politician was influenced by the environment that surrounded him. The idea of symbolic capital allowed us to understand how this subject was seen by the society of his time, considering that he had political support that allowed him to occupy elective positions. The concept of political culture was important to understand how his political thinking was shaped and appropriated by other intellectuals in later historical moments. The idea of conservatism helped to understand how the assumptions of the intellectual had been influenced by the conservative ideal. Finally, the concept of nationalism was mobilized in order to identify how the author contributed to the formation of a Brazilian nationalist thought, since he stood out for writing in this way. Thus, the proposal of the research was to contribute to the field of Brazilian Intellectual History and Political Thought, insofar as the focus of the work is to highlight how an intellectual of the First Republic dealt with ideas and concepts of his time, presenting consonances and dissonances before the environment in which he was inserted, through agreement and criticism.